2022
DOI: 10.3389/fgene.2022.816173
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Potential Roles of m5C-Related Regulators in Colon Adenocarcinoma Prognosis

Abstract: Objectives: The purpose of this study was to investigate the role of 13 m5C-related regulators in colon adenocarcinoma (COAD) and determine their prognostic value.Methods: Gene expression and clinicopathological data were obtained from The Cancer Genome Atlas (TCGA) datasets. The expression of m5C-related regulators was analyzed with clinicopathological characteristics and alterations within m5C-related regulators. Subsequently, different subtypes of patients with COAD were identified. Then, the prognostic val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Increasing evidence suggested that m5C modification plays an indispensable role in both physiological and pathological processes, particularly in the development and progression of cancer (42). Many studies have explored the roles of m5C regulatory genes and constructed prognostic models in colon adenocarcinoma, hepatocellular cancer, cervical cancer, and clear cell renal cell carcinoma (43)(44)(45). However, there were a few studies that investigated the biological role of m5C regulatory genes in PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggested that m5C modification plays an indispensable role in both physiological and pathological processes, particularly in the development and progression of cancer (42). Many studies have explored the roles of m5C regulatory genes and constructed prognostic models in colon adenocarcinoma, hepatocellular cancer, cervical cancer, and clear cell renal cell carcinoma (43)(44)(45). However, there were a few studies that investigated the biological role of m5C regulatory genes in PCa.…”
Section: Discussionmentioning
confidence: 99%
“…To determine subgroups of GC, we used the R package “ConsensusClusterPlus” for the consistent clustering based on the expression pattern of prognostic m 6 AIGs as the previous study ( 32 ). Using the K-mean cluster algorithm and the Euclidean squared distance metric, the optimal clustering amount was confirmed by the clustering score.…”
Section: Methodsmentioning
confidence: 99%
“…The neoplastic tendency of the pancreas needs to be identified, and specific non-invasive markers discriminating PanCa from CP or other pancreatic precursor lesions such as pancreatic intraepithelial neoplasia (PanIN), intrapapillary mucinous neoplasia (IPMN) and mucinous cystic neoplasm need to be developed[ 28 ]. Luo et al [ 29 ] documented that cg10673833, a circulating tumor DNA (ctDNA) methylation marker was found to be very sensitive (89.7%) and specific (86.8%) for the detection of colorectal cancer and its associated pre-cancerous lesions.…”
Section: Liquid Biopsy and Its Role In Panca Diagnosismentioning
confidence: 99%